A Mixed Methods Analysis of Community Integration Among Vulnerably Housed and Homeless Individuals - Ecker, John (Université d'Ottawa / University of Ottawa, 2015)
This thesis presents four distinct studies of psychological and social integration of homeless and vulnerably housed individuals. The first study presents a predictive model of psychological integration, defined as a sense of belonging and membership to one’s community. The second study presents a predictive model of social integration, defined as how an individual engages with others in the community. The third study presents a mixed methods comparative analysis of homeless and vulnerably housed individuals with “high” and “low” levels of psychological and social integration. The fourth study presents a reflexive analysis of conducting interviews with homeless and vulnerably housed individuals. Data for this research comes from a two-year longitudinal study conducted in Ottawa, Ontario. Participants were men and women, over the age of 18 (Baseline: N = 397; Follow-up 1: N = 341; Follow-up 2: N = 320) who were either homeless or vulnerably housed at the study’s outset. Quantitative data analyses occurred at Follow-up 1 and 2 and utilized hierarchical multiple regression. Qualitative data analyses used a general inductive approach utilizing a First Cycle and Second Cycle coding method (Saldana, 2009). Social support was a significant predictor of both psychological integration and social integration. Individuals with high levels of social support had high levels of psychological and social integration. Social support proved to be the only predictor to be significantly associated with social integration at both Follow-up 1 and 2. Psychological integration was positively associated with several variables at Follow-up 1 and 2: increased age, living in high quality housing, and residing in a neighbourhood that is perceived as having a positive impact. The mixed methods analysis uncovered several salient themes that affected psychological and social integration, including substance use in one’s housing and neighbourhood, neighbourhood safety and location, and housing quality. The reflexive component of the thesis highlighted the importance of location when conducting interviews and the power dynamics of the interview process. The results are discussed in terms of implications for service delivery and policy.
Keywords: Community integration; Homeless; Vulnerably housed; Psychological integration; Social integration; Interview location